Natural History and Ecology of Mexico and Central America - Hufnagel, Levente (IntechOpen, 2021)
Natural History and Ecology of Mexico and Central America presents an interesting overview of the frontiers of biodiversity and ecological research in the geographical area of Mexico and Central America. Chapters cover such topics as biodiversity and ecology of plant communities, tropical subterranean ecosystems, floating Sargassum species, the endangered species Dioon edule, Kemp's ridley sea turtles, fish and fisheries, urbanization and bats, and food and sustainable diet.